2010
DOI: 10.1007/s10571-010-9614-9
|View full text |Cite
|
Sign up to set email alerts
|

Fasudil Mesylate Protects PC12 Cells from Oxidative Stress Injury via the Bax-Mediated Pathway

Abstract: We previously reported that fasudil mesylate (FM) improves neurological deficit and neuronal damage in rats with ischemia following middle cerebral artery occlusion and reperfusion in vivo. In this study, the properties of FM on hydrogen peroxide (H(2)O(2))-induced oxidative stress insult in cultured PC12 cells as well as the underlying mechanisms were investigated in vitro. Pretreatment with FM (5, 10 μM) prior to H(2)O(2) exposure significantly elevated cell viability, reduced cell apoptosis by MTT assay, LD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 31 publications
2
5
0
Order By: Relevance
“…ROCK inhibitor-induced apoptosis was shown to be Bcl-2 sensitive, and Bcl-2 families are known to affect cell apoptosis by regulating the permeability of mitochondria [34,35]. In addition, fasudil [20]. We confirmed that fasudil increased Bax, caspase-9, and caspase-3 protein levels in a dose-dependent manner, suggesting that fasudil-induced HCC cell apoptosis is mediated via the mitochondrial pathway.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…ROCK inhibitor-induced apoptosis was shown to be Bcl-2 sensitive, and Bcl-2 families are known to affect cell apoptosis by regulating the permeability of mitochondria [34,35]. In addition, fasudil [20]. We confirmed that fasudil increased Bax, caspase-9, and caspase-3 protein levels in a dose-dependent manner, suggesting that fasudil-induced HCC cell apoptosis is mediated via the mitochondrial pathway.…”
Section: Discussionsupporting
confidence: 58%
“…It was reported that fasudil induces apoptosis through the mitochondrial pathway in cardiomyocytes in cardiac infarction [20]. Western blotting showed the expression of apoptosis-related proteins associated with the mitochondrial pathway in HCC cells cultured with fasudil (50-200 ng/ml (Fig.…”
Section: Effects Of Fasudil On Apoptosis-related Protein Expression Imentioning
confidence: 88%
“…Nonetheless, these changes were significantly reversed by fasudil pre-treatment. Our findings are consistent with a recent report from Li et al showing that restoration of the levels of some apoptotic markers, such as Bcl-2, and Bax play an important role in the neuroprotective effects of fasudil mesylate (25). Taken together, our data not only confirmed previous reports that apoptosis produces retinal cell death after I/R injury, but also demonstrated that fasudil could prevent the apoptosis of retinal cells.…”
Section: Discussionsupporting
confidence: 93%
“…). Primarily, ephrin receptor signaling, the binding of a membrane‐bound EphA5 ligand on a neighboring cell to an EphA receptor, renders the receptor active which induces forward signaling via its kinase domain . Consequently, this recruits several signaling molecules which cluster into a signaling complex that can activate two GEFs, either Ephexin or Vms‐Rho.…”
Section: Introductionmentioning
confidence: 99%
“…Once GEF is active, this further activates RhoA, which stimulates a downstream Rho‐associated kinase (ROCK) signaling pathway by binding to the Rho‐binding domain (RBD) of ROCK. Ultimately, this leads to blocking of nerve fiber growth .…”
Section: Introductionmentioning
confidence: 99%